If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9/8=g+4/8
We move all terms to the left:
9/8-(g+4/8)=0
We add all the numbers together, and all the variables
-(+g+4/8)+9/8=0
We get rid of parentheses
-g-4/8+9/8=0
We multiply all the terms by the denominator
-g*8-4+9=0
We add all the numbers together, and all the variables
-g*8+5=0
Wy multiply elements
-8g+5=0
We move all terms containing g to the left, all other terms to the right
-8g=-5
g=-5/-8
g=5/8
| 4(7-n)=5n-8 | | -9.1(-7r-20)=-13 | | 3x=+4=-11 | | 3(y+2+2(y-3=15 | | 2(x5)-8=34 | | 12=y-5/4. | | Z+40=5z | | -9x+3=-10+10 | | -2h+4h=18 | | 120.5=5z. | | 0.15+23=0.19x | | t-7+3t=-2+4t-5 | | 5y-6=y+42 | | -2h+4=18 | | 3n2+7n=20 | | 6n+7=-20 | | 22=4K+7k | | 3i=-21 | | -2v9=25 | | 4x=84. | | -3x+-5=6 | | 12s-45=s+43 | | 460-45x=100 | | 2x-(3x-5)=4(-x-1) | | 6x+4-4x=35-3x-6 | | y-9/4=7. | | Y=6.5x+25 | | -10+21x=-15x+26 | | (½)(6x-8)=41 | | x/3-300=250 | | 4−5v=−11 | | 5x+7=10x-13= |